Remote Work: Transformations and Tensions in Organizational Commitment And Job Satisfaction (GEON Journal (Management, Organizations and Business), 2026)
Remote work has become a predominant employment modality as a result of technological advances and recent socioeconomic transformations. However, its expansion has generated tensions in organizational commitment and job satisfaction by altering the dynamics of interaction, control, and belonging within organizations. Objective: To analyze, through a systematic review, how remote work influences organizational commitment and job satisfaction, identifying the main factors that strengthen or weaken this relationship. Materials and Methods: The PRISMA model was applied to ensure transparency and rigor in the selection and analysis of studies. The search included international academic databases and focused on empirical research published between 2015 and 2025. Results: The findings indicate that job autonomy, flexibility, and technological support act as positive predictors of commitment and satisfaction, fostering productivity and well-being. In contrast, role ambiguity, digital overload, and social isolation were identified as risk factors that undermine organizational cohesion and the sense of belonging. Conclusion: The effectiveness of remote work depends on management strategies that promote clear communication, social integration, and work–life balance, while recognizing the diversity of contexts and work experiences. Contribution/originality: This study provides an updated and critical synthesis of empirical evidence on the relationship between remote work, organizational commitment, and job satisfaction, offering a conceptual foundation for the design of adaptive and sustainable organizational policies in hybrid or fully remote work environments.
Keywords: Well-being, management, innovation, staff.